2018
DOI: 10.1111/jog.13650
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for severe maternal complications associated with hypertensive disorders after 36 weeks’ gestation in uncomplicated twin pregnancies: A prospective cohort study

Abstract: Severe maternal HD and related complications increased from late preterm to early term; particularly, patients with gestational proteinuria were at high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The difference between the incidence of hypertensive disorders of pregnancy in the PA group and the control group was not significant. It might be significant in a larger study group, as reported by numerous literature results [9][10][11][12][13]. This confirms the possible common etiopathology of both conditions.…”
Section: Group Characteristics and Placental Abruption Risk Factorssupporting
confidence: 83%
See 1 more Smart Citation
“…The difference between the incidence of hypertensive disorders of pregnancy in the PA group and the control group was not significant. It might be significant in a larger study group, as reported by numerous literature results [9][10][11][12][13]. This confirms the possible common etiopathology of both conditions.…”
Section: Group Characteristics and Placental Abruption Risk Factorssupporting
confidence: 83%
“…PA in a previous pregnancy, particularly in cases with a history of multiple PAs, is one of the strongest and most unquestionable PA risk factors [8,9]. Numerous studies also confirmed hypertensive disorders of pregnancy to be one of the most important risk factors for PA [9][10][11][12][13]. The maternal medical history of other chronic diseases is also relevant [14][15][16][17], as are several genetic factors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Existing data suggest an increased risk of maternal and perinatal adverse outcomes in women with HDP compared to women without HDP [15,17,19,20]. Several demographic (age, education, rural domicile), medical (pre-existing hypertension, multiparity, gestational age at delivery) and management (timing of drug administration) characteristics have been identified as risk factors for adverse perinatal and maternal outcomes among women with HDP [9- 11,14,15,[21][22][23]. However, it is unknown if similar rates of adverse outcomes and risk factors persist in a mostly rural population.…”
Section: Introductionmentioning
confidence: 99%
“…Potential PE-associated factors were selected, according to previous studies of hypertensive disorders in singleton and/or twin pregnancies, including: maternal age, 8-10 parity, maternal pre-pregnancy body mass index, [9][10][11] assisted reproductive technology, 12 a family history of hypertension, 8,10 chorionicity, 7,13 maternal weight gain during pregnancy, 14 gestational diabetes mellitus, 9,10,15 and gestational proteinuria (≥300 mg/day). 16 Univariate analysis was used to estimate the crude odds ratios (ORs) and 95% CIs of perinatal factors. The variance inflation factor was calculated, using regression analysis, to confirm multicollinearity.…”
Section: Methodsmentioning
confidence: 99%